The effect of anaerobic exercises with resistance ropes for the arms to develop speed endurance and achievement for the 100-meter freestyle swimmers - Mohammed Farhan, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
Sports training, its rules and training methods have an impact on the development and development of the players' qualities and abilities (physical, physiological, psychological, etc.), whether in individual and group events and games, and in specialized activities. And that the sport of swimming and its effectiveness requires speed in performance in order to cut the distance of the race in the shortest possible time. Undoubtedly, it needs to develop and train the physical qualities and capabilities to achieve good performance and achievement. The importance of the research is to identify the effect of anaerobic exercises with resistance ropes for the arms to develop the endurance of speed and achievement for the 100-meter freestyle swimmer. After presenting, analyzing and discussing the results, the most important conclusions were that anaerobic exercises have a positive effect in developing the selected physical ability (endurance of speed) under research and achieving achievement in the least possible time.